The core functions and forms paradigm throughout EPIS: designing and implementing an evidence-based practice with function fidelity - Terrana, Alec; Viglione, Clare; Rhee, Kyung; Rabin, Borsika; Godino, Job; Aarons, Gregory A.; Chapman, Jessica; Melendrez, Blanca; Holguin, Margarita; Osorio, Liliana; Gidwani, Pradeep; Juarez Nunez, Cynthia; et al. (Frontiers in Health Services, 2024)
There are numerous frameworks for implementing evidence-based practices (EBPs) in novel settings to achieve “fidelity.” However, identifying appropriate referents for fidelity poses a challenge. The Core Functions and Forms paradigm offers a model that can inform adaptation decisions throughout all phases of the Exploration, Preparation, Implementation, Sustainment (EPIS) framework. We applied the Core Functions-Forms paradigm throughout the Exploration and Preparation phases of EPIS in the design of two EBPs targeting family protective factors among Latinos in San Diego, as well as describe plans for its use in Implementation and Sustainment. We employed a distinct approach for each intervention element to contrast adaptation decisions that prioritize adherence to either form or function fidelity. We describe our application of the functions-forms paradigm within the EPIS framework, focusing on the Preparation phase. We also provide functions-forms matrices that map out the relationship between individual intervention components (forms) and the essential processes (functions) by which components are theorized to exert their impact. This case study of how the core functions-forms framework can be mapped onto EPIS can support a conceptual shift from prioritizing form fidelity to also focusing on function fidelity. This might allow interventionists to target appropriate fidelity referents when adapting an EBP, rather than defaulting to maintaining fidelity to forms as described in the protocol. We see great promise for using this framework for guiding actions throughout all EPIS phases and informing future applications of this paradigm to foster more robust fidelity to function.